Mitochondria: Novel Mechanisms and Therapeutic Targets for Secondary Brain Injury After Intracerebral Hemorrhage - Chen, Weixiang; Guo, Chao; Feng, Hua; Chen, Yujie (Frontiers in Aging Neuroscience, 2021)
Intracerebral hemorrhage (ICH) is a destructive form of stroke which often resulting in death or disability. And the survivors usually experience sequelae of neurological impairment and psychiatric disorders, which affect their daily functionality and working capacity. Recently, the recent MISTIE III and STICH II trials have confirmed that early surgical clearance of hematomas does not improve the prognosis of survivors of ICH, so it is urgent to find the intervention target of secondary brain injury after ICH. Mitochondrial dysfunction, which may be induced by oxidative stress, neuroinflammation, and autophagy, among others, is considered to be a novel pathological mechanism of ICH. Moreover, mitochondria play an important role in promoting neuronal survival and improving neurological function after hemorrhagic stroke. This review summarizes the mitochondrial mechanism involved in the cell death, reactive oxygen species production, inflammatory activation, blood-brain barrier disruption and brain edema underlying ICH. We emphasize the potential of mitochondrial protection as a potential therapeutic target for secondary brain injury after stroke and provide valuable insight into clinical strategies.